Liposomal Drug Delivery Systems for Cancer Therapy: The Rotterdam Experience - Mohamadreza Amin; Ann L. B. Seynhaeve; Majid Sharifi; Mojtaba Falahati; Timo L. M. ten Hagen (MDPI AG, 2022)
At the Nanomedicine Innovation Center (NICE) at the Erasmus MC in Rotterdam, we have approached the treatment of cancer by starting with a vision of first establishing a platform that enables us to overcome the low levels of drugs delivered to tumors and the issue of dose-limiting toxicity. Showing that a reduction of the volume of distribution, and a lowering of toxicity and side-effects, accompanied by augmented intratumoral drug delivery, could change outcomes in patients, paved the way to target, not only localized disease, but also systemic and metastasized cancers. In particular, the detailed studies with intravital microscopy we performed at NICE provided us with the necessary insights and affected to a large extent our program on liposome-based cancer therapy. Together with our experience with the loco-regional treatment of cancer, this helped us to develop a program that focused on the subsequent aspects discussed here. We recognized that passive accumulation of nanoparticles was not as effective as previously believed and undertook to improve the local accumulation by changing the tumor pathophysiology and, in particular, the vascular permeability. We added the targeting of liposomes using vascular and tumor directed moieties, to improve cellular drug delivery. To improve payload delivery, we studied the modification of liposomes with phospholipids that help passive drug release and augment cellular accumulation. Second, and importantly, modification of liposomes was undertaken, to enable triggered drug release. The capability for modifying liposomes to respond to a trigger, and the ability to now apply an external trigger (e.g., hyperthermia) and specifically reach the tumor volume, resulted in the current smart drug delivery systems. Our experience at NICE, after a few decades of research on lipid-based nanoparticles, shows that, after the first liposomal formulation registered for clinical application in cancer therapy, further developments quickly followed, while further clinical applications lagged behind. Now we need to focus on and make the next steps towards the clinic, to fulfil the promise that is found there.